Knowledge, Attitude, and Practice toward COVID-19 Infections among Preclinical Medical Students in a Public University in Depok, Indonesia - Pratiwi, Marrisa Indah; Sugiharto, Agus; Friska, Dewi (Poltekkes Kemenkes Palu, 2024)
Preclinical medical students have a big role as agents of change to raise awareness of the pandemic caused by Coronavirus Disease 2019 (COVID-19) infection in family, friends, and society. This study aims to determine the final stage of preclinical medical students' knowledge, attitudes, and practices (KAP) toward COVID-19 infection. This study used a cross-sectional method that was conducted on 213 final-stage preclinical medical students in a public university in Depok, Indonesia using an online validated KAP Questionnaire that measures age, gender, domicile, class, and level of KAP toward COVID-19 infection. Data were analyzed using SPSS 21. The p-value <0.05 indicates statistical significance. The result KAP of students toward COVID-19 infection showed a good level of knowledge (73.7%), positive attitude (96.2%), and positive Practice (83.6). %). There was no relationship between the level of knowledge and attitudes toward COVID-19 infection because a p-value of 0.211 (p >0.05) was obtained. Meanwhile, there was a relationship between the level of knowledge and practice toward COVID-19 infection with a p-value = 0.044 (p <0.05). The results revealed that the majority of preclinical medical students had favorable attitudes, had adequate knowledge of COVID-19, and used effective practices to stop the transmission of the disease.